Public administration : 25 years of analysis and debate - Rhodes, R. A. W. (Wiley-Blackwell, 2011)
Features a history of the evolution of Public Administration over the past 25 years * Provides highly cited source material of proven quality in a single volume * Represents an ideal supplementary reader for any public administration and public management course